Hubungan Ekspresi CD117 dan Epidermal Growth Factor Receptor (EGFR) terhadap Grading Histopatologi Adenoid Cystic Carcinoma pada Kelenjar Liur - Delyuzar; Ren Astrid Allail Siregar; T. Ibnu Alferraly (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundTend to have adenoid cystic carcinoma (AdCC) is one of malignant epithelial tumor of the salivary gland poor prognosis, localrecurrence and metastases. Histopathological grading system according Weert, et al. observed from presence or absence solidcomponent of AdCC. CD117 is a transmembrane tyrosine kinase receptor usually strong expression in AdCC. EGFR belongs to theErbB family of receptor tyrosine kinases associated with cell proliferation, angiogenesis and metastases. Patients with advanceddisease may benefit from targeted therapy besides conventional management. Expression of CD117 and EGFR may give proposaltherapy through difference histology pattern of AdCC based on histopathological grading.MethodsThis is an analytical descriptive study with cross sectional approach. Formalin-fixed paraffin-embedded sections from 35 adenoidcystic carcinomas were obtained for histopathological grading and for immunostained of CD117 and EGFR using monoclonalantibodies. The staining intensity and percentage of cells with membranous and cytoplasmic of CD117 and EGFR expression werescored and then grouped according to the parameters of the Allred scoring system.ResultsChi-square test between CD117, EGFR expression and histopathological grading of AdCC showed no sigficant differences.Besides, McNemar test between CD117 and EGFR expression and histopathological grading AdCC showed significant differences,p-value=0.03 (p<0.05).ConclusionsCD117 and EGFR could be used to detected salivary gland AdCC